(untitled) (Archives of Criminology, 2024)
Dating back to Italy’s first comprehensive immigration law in the 1990s, the practice of detaining irregular migrants has served various explicit and implicit purposes, both practical and symbolic. Two decrees passed in 2023, under the far-right government of Giorgia Meloni, were explicitly framed as responses to the increasing number of migrants arriving at the borders. The aim of these decrees was to prolong the detention of asylum seekers and irregular migrants, with the stated aim of increasing returns. However, despite these measures, available data suggests that the capacity of detention centres has not increased significantly, and the rate of returns has remained stable. Against this backdrop, this article seeks to explore the explicit and implicit functions of detention by examining recent reforms and publicly available quantitative data obtained through a request under Italy’s Freedom of Information Act. It suggests that whilst detention serves practical purposes for a minority of migrants, its symbolic role in conveying state sovereignty and strict border control is equally important.